Endothelin‐A receptor in gastric cancer and enhanced antitumor activity of trastuzumab in combination with the endothelin‐A receptor antagonist ZD4054. Issue 1 (2nd April 2019) - Shen, Weisong; Xi, Hongqing; Li, Chenyang; Bian, Shibo; Cheng, Haidong; Cui, Jianxin; Wang, Ning; Wei, Bo; Huang, Xiaohui; Chen, Lin
Abstract: Endothelin‐A receptor (ETAR) is overexpressed in cancers and can function through transactivation of the epidermal growth factor receptor. We explored ETAR in gastric cancer and investigated the antitumor effect of trastuzumab in combination with the ETAR antagonist ZD4054. The expression of ETAR was significantly correlated with the expression of vascular endothelial growth factor. Univariate and multivariate analyses further showed that ETAR expression correlated with reduced survival in gastric cancer patients. In vitro, ZD4054 increased the antiproliferative effect of trastuzumab in gastric cancer cell lines. Moreover, the addition of ZD4054 to trastuzumab significantly increased apoptosis in gastric cancer cell lines. In vivo, tumor growth was considerably inhibited by treatment with ZD4054 and trastuzumab, and the tumor volume in the trastuzumab and ZD4054 combination group was smaller than in the other groups. The detection of ETAR could help predict the prognosis of gastric cancer patients. Additionally, this study provides support for the therapeutic use of the combination of ZD4054 and trastuzumab as an anticancer treatment, especially for gastric cancer. Abstract : Endothelin‐A receptor (ETAR) is overexpressed in cancers and can function through transactivation of the epidermal growth factor receptor (EGFR). This paper examines ETAR expression in gastric cancer and investigates the antitumor effect in vitro and in vivo on gastric cancer of the EGFR antagonist trastuzumab in combination with the ETAR antagonist ZD4054.